2019
DOI: 10.1164/rccm.201905-1071st
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation and Management of Obesity Hypoventilation Syndrome. An Official American Thoracic Society Clinical Practice Guideline

Abstract: ; on behalf of the American Thoracic Society Assembly on Sleep and Respiratory Neurobiology THIS OFFICIAL CLINICAL PRACTICE GUIDELINE OF THE AMERICAN THORACIC SOCIETY WAS APPROVED MAY 2019 Background: The purpose of this guideline is to optimize evaluation and management of patients with obesity hypoventilation syndrome (OHS). Methods: A multidisciplinary panel identified and prioritized five clinical questions. The panel performed systematic reviews of available studies (up to July 2018) and followed the Grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
158
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(184 citation statements)
references
References 116 publications
0
158
0
26
Order By: Relevance
“…48 OSA is a component of obesityhypoventilation, presenting with respiratory failure in more than 85% of cases, and most patients with a clinical diagnosis of this syndrome are treated in the long term with positive airway pressure for sleep-disordered breathing. 49 Conversely, only selected groups of COPD patients with persistent hypercapnia after an exacerbation benefit from home NIV, as evidenced by recent high quality, randomized controlled trials. 50,51 Yet, cohort studies suggest that untreated COPD patients with comorbid OSA are at increased risk of repeated exacerbations and death.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…48 OSA is a component of obesityhypoventilation, presenting with respiratory failure in more than 85% of cases, and most patients with a clinical diagnosis of this syndrome are treated in the long term with positive airway pressure for sleep-disordered breathing. 49 Conversely, only selected groups of COPD patients with persistent hypercapnia after an exacerbation benefit from home NIV, as evidenced by recent high quality, randomized controlled trials. 50,51 Yet, cohort studies suggest that untreated COPD patients with comorbid OSA are at increased risk of repeated exacerbations and death.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Despite this knowledge, the diagnosis of OHS is relatively uncommon. The use of serum bicarbonate as a screening test can be helpful to prioritize on which patients to consider daytime arterial blood gas sampling . The argument has been ongoing about whether the diagnosis of OHS versus OSA actually changes clinical management.…”
Section: Non‐invasive Ventilationmentioning
confidence: 99%
“…First, several studies have shown that a major proportion of OHS patients present decompensated in the intensive care unit, making the recent Lancet findings not applicable to such patients . A recent American Thoracic Society (ATS) clinical practice guideline on the evaluation and management of OHS recommended acute NIV therapy for these patients with hospital to home transition until they can undergo outpatient diagnostic testing . Second, some suggestive data have shown potential improvements in pulmonary haemodynamics with bi‐level as compared to standard CPAP, suggesting that an OHS diagnosis may change management in some cases .…”
Section: Non‐invasive Ventilationmentioning
confidence: 99%
“…Obesity Hypoventilation Syndrome (OHS) is a sleep-related hypoventilation disorder characterized by obesity (body mass index, BMI ≥30 kg/m 2 ) and daytime hypercapnia (resting arterial carbon dioxide tension ≥45 mmHg at sea level). Ninety percent of cases are associated with Obstructive Sleep Apnea (OSA); in the remaining percentage of patients no obstructive events are found [1]. Ruling out other causes of hypoventilation, such as Chronic Obstructive Pulmonary Disease (COPD), is a key element in the definition of OHS.…”
mentioning
confidence: 99%
“…In early stages, there is not daytime hypercapnia and these patients can be recognized by increased levels of serum bicarbonate [2]. OHS is the most severe form of obesityinduced respiratory disease and causes serious clinical sequelae such as increased rates of mortality, chronic heart failure, pulmonary hypertension, and acute-on-chronic hypercapnic respiratory failure, all causes potentially leading to hospitalizations even in Intensive Care Unit (ICU) [1]. However, despite the increasing attention towards this disease and the growing number of dedicated studies, the OHS prevalence in the general population remains uncertain.…”
mentioning
confidence: 99%